A Clinical Pharmacology and Therapeutics Teacher's Guide to Race‐Based Medicine, Inclusivity, and Diversity. Issue 3 (23rd November 2022) - Bakkum, Michiel J.; Verdonk, Petra; Thomas, Elias G.; van Rosse, Floor; Okorie, Michael; Papaioannidou, Paraskevi; Likic, Robert; Sanz, Emilio J.; Christiaens, Thierry; Costa, João N.; Dima, Lorena; de Ponti, Fabrizio; et al.
Abstract : The relationship between race and biology is complex. In contemporary medical science, race is a social construct that is measured via self‐identification of study participants. But even though race has no biological essence, it is often used as variable in medical guidelines (e.g., treatment recommendations specific for Black people with hypertension). Such recommendations are based on clinical trials in which there was a significant correlation between self‐identified race and actual, but often unmeasured, health‐related factors such as (pharmaco)genetics, diet, sun exposure, etc. Many teachers are insufficiently aware of this complexity. In their classes, they (unintentionally) portray self‐reported race as having a biological essence. This may cause students to see people of shared race as biologically or genetically homogeneous, and believe that race‐based recommendations are true for all individuals (rather than reflecting the average of a heterogeneous group). This medicalizes race and reinforces already existing healthcare disparities. Moreover, students may fail to learn that the relation between race and health is easily biased by factors such as socioeconomic status, racism, ancestry, and environment and that this limits the generalizability of race‐based recommendations. We observed that the clinical case vignettes that we use in our teaching contain many stereotypes and biases, and do not generally reflect the diversity of actual patients. This guide, written by clinical pharmacology and therapeutics teachers, aims to help our colleagues and teachers in other health professions to reflect on and improve our teaching on race‐based medical guidelines and to make our clinical case vignettes more inclusive and diverse.